Appeal of the decision in the case of administrative offenses as part of the rights guarantees citizens to protection - Горкава, Влада Владиленівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
Author in the article considers the appeal of the decision in the case of administrative offenses, as an element of the rights guarantees citizens to protection. It was found that the appeal of the decision in the administrative case is essential to exercise their right to protection interests. This is effective action to eliminate the errors the application of substantive law.